A Possible Dark Side of Listening? Teachers Listening to Pupils Can Increase Burnout - Eli Vinokur; Guy Itzchakov; Avinoam Yomtovian (MDPI AG, 2024)
A growing body of the literature on interpersonal listening has revealed numerous positive outcomes in the workplace. For example, employees who listen well are perceived as leaders, perform better at work, gain trust, and succeed in negotiations, among other benefits. However, there is a gap in the literature regarding the potential negative consequences of listening in the workplace, especially when it is effortful and challenging. This study explored the potential relationship between teachers listening to their pupils and burnout. Conducted in 2024, this field study involved 106 middle and high school teachers from Israel. We used multiple regression analysis to control for well-known predictors of job burnout: motivation, job satisfaction, and competence. The results indicated that teachers' perception of their listening quality significantly and positively predicted job burnout, even when accounting for these variables as well as seniority and school-type; 0.24 ≤ βs ≤ 0.36. This study highlights the potential negative consequences of workplace listening and contributes to the less explored aspect of listening in the literature with important implications for work-related outcomes.